Higher risk of cardiovascular mortality than cancer mortality among long-term cancer survivors - Wang, Zhipeng; Fan, Zeyu; Yang, Lei; Liu, Lifang; Sheng, Chao; Song, Fengju; Huang, Yubei; Chen, Kexin (Frontiers in Cardiovascular Medicine, 2023)
Background: Previous studies focused more on the short-term risk of cardiovascular deaths related to traumatic psychological stress after cancer diagnosis and acute cardiotoxicity of anticancer treatments, but less on the long-term risk of cardiovascular death. Methods: Temporal trends in the proportions of cardiovascular death (PCV), cancer death (PCA), and other causes in all-cause deaths were used to show preliminary relationships between three causes of death in 4,806,064 cancer patients from the the Surveillance, Epidemiology, and End Results (SEER) program. Competing mortality risk curves were used to investigate when cumulative cardiovascular mortality rate (CMRCV) began to outweigh cumulative cancer mortality rate (CMRCA) for cancer patients survived more than 10 years. Multivariable competing risk models were further used to investigate the potential factors associated with cardiovascular death. Results: For all-site cancer patients, the PCV increased from 22.8% in the 5th year after diagnosis, to 31.0% in 10th year, and 35.7% in the 20th year, while the PCA decreased from 57.7%, to 41.2% and 29.9%, respectively. The PCV outweighed the PCA (34.6% vs. 34.1%) since the 15th year for all-site cancer patients, as early as the 9th year for patients with colorectal cancer (37.5% vs. 33.2%), as late as the 22nd year for patients with breast cancer (33.5% vs. 30.6%). The CMRCV outweighed CMRCA since the 25th year from diagnosis. Multivariate competing risk models showed that increased risk of cardiovascular death was independently associated with elder age at diagnosis[Hazard ratio and 95% confidence intervals of 43.39(21.33, 88.28) for ≥80 years vs. ≤30 years] and local metastasis [1.07(1.04, 1.10)], and decreased risk with female [0.82(0.76, 0.88)], surgery [0.90(0.87, 0.94)] and chemotherapy [0.85(0.81, 0.90)] among cancer patients survived more than 10 years. Further analyses among cancer patients survived more than 20 years and sensitivity analyses by cancer sites showed similar results. Conclusions: Cardiovascular death will gradually outweigh cancer death as survival time increases for most cancer patients. Both cardio-oncologist and cardio-oncology care should be involved to reduce cardiovascular deaths in long-term cancer survivors.